2023
DOI: 10.1177/14651165231175533
|View full text |Cite
|
Sign up to set email alerts
|

European by action: How voting reshapes nested identities

Abstract: Although research has questioned the stability of identities, we know little about identity change. I examine a political event as a driver of identity change, namely the Brexit vote. I contend that the act of voting, choosing between two options, boosts the European and British identity underlying the vote choice. I test whether the increased identification with Europe or Britain comes with a reduction in the other identity. Using British Election Study panel data in a two-way fixed-effects design, I show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 70 publications
1
5
0
Order By: Relevance
“…Table 1 provides summary statistics of the key variables used in our analysis. 9 As can be seen in this table, the average strength score for both Britishness and Nationness is very high (5.6 on the 1-7 scale), in line with BritonsŠ long-lasting tradition of holding multiple salient national identities (Sczepanski, 2023). However, when we split the sample by nation, we can observe some notable differences in how the two identities are perceived.…”
Section: Data and Sampling Proceduressupporting
confidence: 52%
See 3 more Smart Citations
“…Table 1 provides summary statistics of the key variables used in our analysis. 9 As can be seen in this table, the average strength score for both Britishness and Nationness is very high (5.6 on the 1-7 scale), in line with BritonsŠ long-lasting tradition of holding multiple salient national identities (Sczepanski, 2023). However, when we split the sample by nation, we can observe some notable differences in how the two identities are perceived.…”
Section: Data and Sampling Proceduressupporting
confidence: 52%
“…As such, terrorism could bolster support for ethnic and regional identities. Considering that individuals in Britain hold multiple national identities, which are often seen as complementary and compatible (Denham and Devine, 2017;Sczepanski, 2023), this could result in a simultaneous reinforcement of all of them.…”
Section: Supranational Unity and National Identitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Deutsch (1957) argued that transnational contacts and interactions contribute to the adoption of European identities, and subsequent research has shown that experiences such as participating in Erasmus programs and residing in diverse neighborhoods foster the growth of European identity (Kuhn, 2011; Schraff & Sczepanski, 2022; Stoeckel, 2016, but see Kuhn, 2012). Moreover, symbols representing the European Union and pro-European actions have been demonstrated to be related to the adoption of a European identity (Nicoli et al, 2020; Sczepanski, 2023a). The notable success of socialization approaches is unsurprising, as the fundamental functions of identities are social in nature, creating a sense of belonging.…”
Section: The Development Of Political Identities In the Socio-structu...mentioning
confidence: 99%